Efektivitas Penggunaan Alat Permainan Edukatif Tabung Berhitung untuk Mengembangkan Kemampuan Berhitung Anak Usia 5–6 Tahun di RA Al-Hidayah - Nurdiani, Silfi (Lembaga Yasin AlSys, 2025)
Numeracy skills are a crucial aspect of cognitive development in early childhood and must be cultivated through engaging learning approaches that align with children's developmental characteristics. At RA Al-Hidayah, learning remains predominantly conventional, often resulting in passive participation and reduced engagement, thereby limiting optimal understanding of number concepts. This study aims to analyze the effectiveness of the educational game tool Tabung Berhitung (Counting Tube) in improving the numeracy skills of children aged 5–6 years. A quantitative approach was employed using a pre-experimental one-group pretest-posttest design. The research subjects consisted of 15 Group B children selected through total sampling. Data collection techniques included observation, pretest and posttest assessments, interviews, and documentation. Data were analyzed using the paired sample t-test. The results showed an increase in the average score from 9.07 (pretest) to 18.33 (posttest), with a significance value of 0.000 (< 0.05), indicating a statistically significant difference after the use of the media. The children demonstrated improvement in number sequencing, counting concrete objects, and matching number symbols to quantities. The study concludes that the Tabung Berhitung is effective in enhancing early childhood numeracy skills. The implications highlight the importance of integrating concrete and enjoyable educational play tools into early childhood education strategies to promote active, contextual, and meaningful numeracy learning.